Helicon discharge excited by a planar antenna in bounded volume - Virko, V.F.; Slobodyan, V.M.; Shamrai, K.P.; Virko, Yu.V. (Вопросы атомной науки и техники, 2014)
By direct spatial measurements of wave RF magnetic fields it is confirmed that the density jumps in the helicon discharge with a flat (planar) antenna result from changes in axial modes of standing helicon waves in a limited volume. In independently produced plasma the planar antenna resistance was measured at various plasma densities n and magnetic fields B0. In the studied range of parameters (n/B0 ≤ 2.5×1020 T−1m−3) the planar antenna impedance increases with the ratio n/B0, in contrast to other types of helicon antennas. The resonances of RF power absorption, caused by standing waves excitation, for the planar antenna are observed at about two times higher values of n/B0 than for the frame m = 1 antenna. Прямыми пространственными измерениями высокочастотных волновых магнитных полей подтверждено, что скачкообразные изменения плотности плазмы в геликонном разряде, возбуждаемом плоской (планарной) антенной, вызываются изменением продольных мод стоячих геликонных волн в ограниченном объёме. В независимо приготовленной плазме измерено сопротивление планарной антенны при различных значениях концентрации плазмы n и магнитного поля B0. В исследованном диапазоне параметров (n/B0 ≤ 2,5×1020 м−3•Tл−1) с увеличением отношения n/B0 сопротивление планарной антенны растёт, в отличие от геликонных антенн других типов. Резонансы поглощения ВЧ-энергии, вызванные раскачкой стоячих волн, у планарной антенны наблюдаются при значениях n/B0 вдвое больших, чем у рамочной m = 1 антенны. Прямими просторовими вимірюваннями високочастотних хвильових магнітних полів підтверджено, що стрибкоподібні зміни густини плазми в геліконному розряді, збуджуваному плоскою (планарною) антеною, спричиняються зміною поздовжніх мод стоячих геліконних хвиль в обмеженому об’ємі. У незалежно утвореній плазмі виміряно опір планарної антени при різних значеннях концентрації плазми n та мангітного поля B0. У дослідженому діапазоні параметрів (n/B0 ≤ 2,5×1020 м−3•Tл−1) зі збільшенням відношення n/B0 опір планарної антени зростає, на відміну від геліконних антен інших типів. Резонанси поглинання ВЧ-енергії, обумовлені розкачкою стоячих хвиль, у планарної антени спостерігаються при значеннях n/B0 вдвічі більших, ніж у рамкової m = 1 антени.